Translanguaging Pedagogies in Digital Learning Environments: Fostering Multilingual Competence Among Generation Z Learners - Muhammad Nur Iman; Nurasia Natsir (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
This paper examines the implementation of translanguaging pedagogies within digital learning environments and their effectiveness in developing multilingual competence among Generation Z learners. Through a mixed-methods study involving 186 students and 14 educators across six higher education institutions, this research investigates how strategic integration of translanguaging practices in digital spaces supports linguistic flexibility, metalinguistic awareness, and cross-cultural competence. Findings reveal that digitally-mediated translanguaging approaches resulted in significant improvements in learners' willingness to communicate across languages (p<.01), metalinguistic awareness (p<.001), and cross-cultural communication efficacy (p<.01) compared to monolingual instructional approaches. The research further identifies five key digital translanguaging strategies that effectively leverage Generation Z's technological aptitude and multimodal literacy. This study contributes to the growing field of multilingual digital pedagogy by demonstrating how translanguaging can be systematically integrated into digital learning environments to foster linguistic repertoire expansion that aligns with the communicative needs of increasingly globalized contexts. The pedagogical framework presented offers practical guidance for educators seeking to implement translanguaging approaches in various digital learning modalities while accommodating Generation Z's learning preferences and multilingual development.